Analisis Penggunaan Kontrasepsi Modern pada Wanita Usia Subur (WUS) Selama Masa Pandemi COVID-19 - Dwi Septianis; Dianita Ekawati; Helen Evelina Siringoringo (Jurnal Kesehatan Saelmakers PERDANA, 2023)
Analysis of the use of modern contraceptives in women of childbearing age during the COVID-19 Pandemic. One indicator of the success of the family planning program is seen in the coverage of the use of modern contraception. The existence of the COVID-19 pandemic in the last two years has had a very large effect on all aspects of life, one of which is in public health services, including contraceptive services. This study aims to analyze the use of modern contraception in women of childbearing age during the COVID-19 pandemic in Ilir Timur I District, Palembang City in 2022. The research design used was cross-sectional with a sample of 96 people taken using a purposive random technique sampling. The statistical tests used were the chi-square test for bivariate analysis and multiple logistic regression for multivariate analysis. The results of this study showed that there was a relationship between education level (p-value 1.00), employment status (p-value 0.00), knowledge of family planning tools/methods (p-value 0.96), access to health facilities (p-value 0.96). 0.55), husband's support (p-value 0.00), and family planning counseling by officers (p-value 0.008). This study concludes that there is a relationship between employment status, husband's support, and family planning counseling by officers with the use of modern contraception during the COVID-19 Pandemic in Ilir Timur I District, Palembang City in 2022. The husband's support variable is the most dominant variable influencing the use of modern contraception with a p-value of 0.00 and OR 40.91. It is recommended to the Ilir Timur I District of Palembang City to involve religious leaders, community leaders, and local traditional leaders in providing communication, information, and education to husbands to provide support to their wives in the use of modern contraception.